Utilization of complete rumen modifier on sheep fed high fibrous forages. - Amlius Thalib; Yeni Widiawati; Budi Haryanto (Indonesian Center for Animal Research and Development (ICARD), 2010)
A research to improve livestock productivity and lower enteric methane production on ruminant was conducted by manipulation approach on rumen system using a complete rumen modifier (CRM). An in vivo experiment was carried out using twenty four sheep ( mean weight 18 kg) which were distributed into 3 treatment groups of feed additive: I. control ( without treatment: K); II: K + CRM-LG; III: K + CRM-EL. Diet given consisted of fermented rice straw (ad libitum) + concentrate containing 16 % protein (400 g/head/day), and drinking water was given ad libitum. The experiment was conducted for 14 weeks based on completely randomized design. By the end of the experiment, animals were placed in the metabolism cages for 2 weeks (ie. 1 week for adaptation and 1 week for data collection). Rumen liquid of each treated animal was taken for the measurement of rumen characteristics. Parameter measuremed were: total gas production; gas composition of CO2 and CH4; in vitro DMD; NH3 and VFA contents; pH; bacterial and protozoal counts; consumption/ DMI; in vivo DMD; ADG and FCR. The results showed that productivity of sheep was improved by CRM treatments followed by lowered enteric methane production. The ADG values of CRM treatments (71.4 to 73.5 g) were significantly higher (P < 0.05) than that of control (50 g). The improvement of average daily gain was followed by a better feed conversion (P < 0.05) (ie. 10.6 vs. 12.8). The CRM treatments lowered the percentage of CH4 by 24% compared to Control (P < 0.05). The total and composition of VFA of CRM-treated rumen liquor were significantly different (P<0.05) compared to that of rumen liquor of Control (ie. the total VFA: 85.3 vs 73.5 mM and the percentage of acetic acid: 67.8 vs 60.3%). It is concluded that CRM treatment resulted in positive effects on growth of ruminant fed high fibrous forages such as rice straw and could lower enteric methane production. Key Words: Rumen Modifier, Productivity, Enteric Methane, Sheep, Rice Straw